A diverse set of solubilized natural fibers drives structure-dependent metabolism and modulation of the human gut microbiota - Maria X. Maldonado-Gomez; Katharine M. Ng; Riley A. Drexler; Alexandria M. S. Conner; Cory G. Vierra; Nithya Krishnakumar; Hannah M. Gerber; Zachary R. Taylor; Jenna L. Treon; Megan Ellis; Jada K. A. Garcia; James P. Cerney; et al. (mBio)
ABSTRACT Growing evidence suggests that inadequate dietary fiber intake, termed the “fiber gap,” is linked to disease states through disruption of the gut microbiota. Despite this, our understanding of how various fiber structures influence the microbiota and health is limited by the lack of diverse commercially available fibers. Studies have primarily focused on a limited range of fibers, rather than the diverse array of fibers representative of those commonly found in our diets. In this study, we aimed to investigate how naturally derived fibers impact the human microbiota and their metabolic products. We performed a comprehensive structural characterization and functional evaluation of a unique and highly diverse set of new, highly soluble fibers with varied monosaccharide compositions, glycosidic linkages, and polymer lengths. Using an ex vivo high-throughput human microbiota platform coupled with metabolomic profiling, we demonstrate that these diverse fibers drive distinct and consistent microbial and metabolic profiles across cohorts of donors in a structure-dependent manner. These metabolic effects were accompanied by both general and donor-specific changes in microbial taxa. Finally, we demonstrate that integrating detailed glycomic characterization with microbial and metabolomic data allowed for prediction of functional outcomes driven by a novel material, pineapple pulp fiber. This work highlights the potential for targeted dietary fiber interventions to modulate the microbiota and improve health outcomes, paving the way for the development of new fiber-rich products with specific health benefits.IMPORTANCEFiber deficiency is associated with numerous disease states, many of which are linked to disruption of the gut microbiota. This study encompasses the first systematic and comprehensive characterization of a diverse collection of naturally derived solubilized fibers and their impacts on the microbiota. The results expand our understanding of the beneficial effects of specific carbohydrate structures naturally found in the human diet, highlighting the potential for designing fiber-based health interventions. The high solubility of these fibers increases both the range of products they can be incorporated in as well as their assayability in experiments, enabling a widespread increase in fiber consumption and positive health impacts.